Gambaran Kadar Rheumatoid Factor (Rf) Pada Wanita Menopause - Liah Kodariah (Jurnal Kesehatan Rajawali, 2022)
Menopause occurs in women aged between 40-55 years. Decreased levels of the hormone estrogen at the time of menopause will interfere with calcium absorption so that bones become brittle. Cells that experience inflammation will cause the entry of antibodies into the space between the bones. In response to antigenic determinants, antibodies from IgG and IgM are formed which are called Rheumatoid Factor (RF). This study was to determine the RF levels in postmenopausal women qualitatively and then to quantitatively. Methods: This research is descriptive with RF examination using latex agglutination method. Sampling was done by purposive sampling of 30 samples. The results of this study were qualitatively 80% negative RF results and 20% positive RF results followed by a semi-quantitative test obtained 4 samples with a titer of 8 IU/mL and 2 samples with a titer of 16 IU/mL. Based on research on the description of RF levels in postmenopausal women, it can be concluded that the positive results of RF 20% and negative results of RF 80%.